Peningkatan Profesional Guru Tentang Pemahaman Pembelajaran Terpadu dalam Muatan IPA Di SD Gugus I Kecamatan Kuranji Padang - Yasman Yasman; Hadiyanto Hadiyanto; Ramalis Hakim (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
Integrated learning has 10 types, one type of integrated learning that is applied in SD is the webbed type integrated in the 2013 curriculum. For this reason, an understanding of the teacher is needed in implementing web type integrated learning in schools. The purpose of this study was to determine the level of teacher understanding of integrated learning in the webbed type of science content in Cluster I Region I, Kuranji District, Padang City. This type of research is qualitative. Based on the distribution of a questionnaire containing 20 statements divided into three parts, it was found that 50% of the teachers understood the types and applications, 84% of the teachers understood the strengths, and 67% of the teachers understood the shortcomings of the webbed type of integrated learning. So the teachers in Cluster I Region I, Kuranji District, Padang City already understand the webbed type integrated learning.